Genes, Gender, Hormones, and Doping in Sport: A Convoluted Tale - Rogol, Alan D.; Pieper, Lindsay Parks (Frontiers in Endocrinology, 2017)
We are writing this piece in the aftermath of the 2016 Olympic Games in Rio de Janeiro, Brazil. Each of the words in the title plays a role(s) in deciding who may compete, especially who may compete as a woman. We shall be careful to disentangle the issues of genes and gender from hormonal levels of the potent androgen testosterone, and very clearly demarcate these natural occurrences from those of doping, for which the World Anti-Doping Agency has established strict guidelines. These elements became conflated in the aftermath of the Court of Arbitration of Sport’s decision, now more than 2 years ago, concerning the teenage Indian sprinter, Dutee Chand. Although many people associate hyperandrogenism with doping and gender determination, each is different and has a distinct function.